A Dynamic Capability Perspective to Understanding the Typology of Big Data Capabilities. Evidence from a Ghanaian Health Insurance Firm - Marfo, John Serbe (Journal of Health Informatics in Africa, 2017)
Big data has become a key competitive advantage tool for firms. Big data is disrupting several markets by causing firm to rethink and change their traditional way of handling and using data within and outside. This makes big data possess dynamic capabilities. Given that only few predominantly big technology firms have been able to fully adopt big data to obtain benefits. This research grounded in the theoretical lens of dynamic capabilities examines the constituents or typology of big data capabilities that are needed by firms to adopt big data. The research proposes a hierarchical model for the typology of big data capabilities which is made up technological capabilities, human skills capabilities and organisational capabilities as the core capabilities of big data capabilities. Beyond the second order capabilities, first-order capabilities and resource base or zero-order capabilities are proposed. An investigation of a health insurance firm implementing big data in Ghana is used to evaluate the suggested model and identify challenges in the development of the big data capabilities as experienced by the health insurance firm.